Waste-to-wealth in ASEAN countries: A case on e-waste generation from mobile phone. Issue 1 (October 2021) - Ismail, H; Hanafiah, M M
Abstract: The aim of this study was to evaluate the potential economic value of e-waste generation in ASEAN countries. The data used in this study was based on various reports. As the reliable information on e-waste generation in ASEAN countries is scarce, the study only evaluated the potential economic value of e-waste generation from mobile phone. The results showed that the potential economic value of e-waste from mobile phone around the world was valued at US$ 18, 545.27 million. For ASEAN countries, it was valued at US$ 2, 019.06 million, higher than 27 developed countries in European Union that valued at US$ 1, 286.59 million. Currently, apart from the ineffective implementation of e-waste regulation, the lack of reliable information and data to estimate e-waste generation and its future projection was a common problem faced by ASEAN countries that impending the development of sustainable e-waste management. Therefore, the potential economic value of e-waste generation in ASEAN countries could be higher, if various other products were included in the analysis with a reliable information and data. Finally, some recommendation was made that includes the need a thorough intergovernmental cooperation and collaboration among ASEAN countries in order to reap a potential economic benefit from continuously growing e-waste in this region.